Perlindungan Hukum terhadap Pihak Swasta pada Kontrak Build Operate Transfer dalam Sengketa Pembatalan Kontrak Sepihak dari Pemerintah - Emir Fabrian Marino; Atik Winanti (Jurnal Interpretasi Hukum, 2023)
The Build Operate Transfer (BOT) scheme has become the primary choice for governments in financing infrastructure due to its significant benefits for both the government and the private sector. However, there are often associated problems and risks, especially regarding unilateral contract cancellations. Hence, legal protection for the parties involved in BOT contracts is crucial due to the substantial investments in long-term infrastructure projects. The type of research used in this study is normative legal research. The author employs approaches including statutory and case law analysis. The author utilizes qualitative juridical data analysis techniques, involving the interpretation of legal materials as an initial step, typically conducted in normative legal research. The results of this study indicate that although BOT contract law in Indonesia has been regulated, there are still several issues in its implementation, often leading to disputes and unilateral contract cancellations. The government must ensure legal certainty for investors and other private sector entities so that the investment climate, including through BOT contracts, can thrive in Indonesia. This principle is then developed into regulations governing legal protection provisions for unilateral contract cancellations. Indonesia's legal framework for BOT contracts is detailed, but some additions are necessary to enhance its effectiveness. Therefore, future BOT legal frameworks are recommended to include general provisions related to BOT projects, tender offers and negotiations, agreement mechanisms, signing processes, and project monitoring.